MENGEMBANGKAN KETERAMPILAN GERAK DASAR MANIPULATIF BAGI ANAK MELALUI PERMAINAN OLAHRAGA DI TAMAN KANAK-KANAK - Jhony Hendra; Ghazali Indra Putra (Jurnal Muara Pendidikan, 2019)
Sports games are one part that can not be separated from human life, through physical education, humans can learn more from things related to affective, cognitive, and psychomotor which are human provisions to achieve better life goals. Manipulative skills are a child's activity related to objects outside of him that must be manipulated in such a way that one skill is formed. The purpose of this study was to determine the teacher's efforts in developing basic manipulative movement skills for children through sports games on the aspects of throwing, catching, kicking and dribbling. This research was conducted using a qualitative descriptive approach (case study) involving 3 teachers. Data collected through observation, interviews, and document analysis. Data were analyzed qualitatively using data reduction, data presentation and drawing conclusions. The results showed that the teacher's efforts in developing basic manipulative movement skills for children through sports games are as follows: 1) providing tools or materials that attract children's attention in developing basic manipulative movement skills through sports games, 2) providing direction and examples to children in develop basic manipulative movement skills through exercise, 3) observe the child during the process of developing basic manipulative movement skills through sports games